Neuroprotective and Anti-Inflammatory Activity of Undaria pinnatifida Fucoidan In Vivo—A Proteomic Investigation - Cheng Yang; Corinna Dwan; Barbara C. Wimmer; Maurizio Ronci; Richard Wilson; Luke Johnson; Vanni Caruso (Marine Drugs)
Undaria pinnatifida fucoidan (UPF), a bioactive sulphated polysaccharide, is widely recognised for its anti-inflammatory, antioxidant, antitumor, anticoagulant, antiviral, and immunomodulatory properties. However, the precise mechanisms by which UPF regulates inflammation and neuronal health remain unclear. This study aimed to investigate the effects of UPF supplementation on pro-inflammatory cytokines in skeletal muscle, small intestine, and the hypothalamus, as well as plasma cytokine levels. Additionally, a brain proteomic investigation in the nucleus accumbens (NAc) was performed to assess UPF’s impact on neuronal protein expression in mice. A total of 64 C57BL/6J mice were administered either a standard chow or high-fat diet (HFD) with or without UPF (400 mg/kg/day) for 10 weeks. In HFD-fed mice, UPF significantly reduced the expression of pro-inflammatory cytokines (TNF-α, IL-1β, and IL-6) in skeletal muscle, small intestine, and hypothalamus, while also lowering circulating IL-1α and IL-6 levels. Proteomic analysis of the NAc revealed that UPF modulated proteins involved in oxidative stress, neuroinflammation, neurotransmitter regulation, and endoplasmic reticulum stress. In contrast, in chow-fed mice, UPF had no effect on the neuroinflammatory–oxidative stress markers but influenced the abundance of proteins associated with immune response and innate immunity. These findings suggest that UPF modulates stress-response pathways in a diet-dependent manner, supporting its potential neuroprotective role in inflammation-related disorders and brain health.